Evolusi perumusan teori akuntansi: dari pendekatan normatif hingga positif dalam konteks praktik kontemporer - Hani, Isma (Maliki Interdisciplinary Journal, 2026)
This study examines the evolution of accounting theory formulation from a normative to a positive approach and its implications for contemporary accounting practice through a comprehensive literature review. Normative accounting theory, which dominated the period from 1956 to 1970, focused on recommendations for how accounting practices should be carried out, but was limited in explaining actual practices. Positive accounting theory, which has developed since 1970, seeks to explain and predict actual accounting behavior through various empirical hypotheses. Recent research reveals that these two approaches are not antagonistic but complementary, integrated in global accounting standards such as IFRS, earnings management, and the implementation of AI technology in auditing. Analysis of the convergence of FASB-IASB standards and the adoption of Ind-AS shows the complexity of applying theory in global and local practice. Contingencies in the implementation of accounting management practices depend on internal-external factors and the specific context of the organization, as evidenced in studies of the hospitality sector during the COVID-19 pandemic. The integration of normative and positive theory with technological innovation creates new opportunities for improving the quality of accounting and auditing. The study concludes that effective accounting theory must integrate normative and positive insights while considering local contexts and technological developments to produce accounting practices that are responsive to the diverse and evolving needs of stakeholders.